Esoteric Pure Land Buddhism - Proffitt, Aaron P. (Pure Land Buddhist studies., 2023)
"What, if anything, is Esoteric Pure Land Buddhism? In 1224, the medieval Japanese scholar-monk Dohan (1179-1252) composed The Compendium on Esoteric Mindfulness of Buddha (Himitsu nenbutsu sho), which begins with another seemingly simple question: Why is it that practitioners of mantra and meditation rely on the recitation of the name of the Buddha Amitabha? To answer this question, Dohan explored diverse areas of study spanning the whole of the East Asian Mahayana Buddhist tradition. Although contemporary scholars often study Esoteric Buddhism and Pure Land Buddhism as if they were mutually exclusive, diametrically opposed, schools of Buddhism, in the present volume Aaron Proffitt examines Dohan's Compendium in the context of the eastward flow of Mahayana Buddhism from India to Japan and uncovers Mahayana Buddhists employing multiple, overlapping, so-called esoteric approaches along the path to awakening. Proffitt divides his study into two parts. In Part I he considers how early Buddhologists, working under colonialism, first constructed Mahayana Buddhism, Pure Land Buddhism, and Esoteric Buddhism as discrete fields of inquiry. He then surveys the flow of Indian Buddhist spells, dharaṇi, and mantra texts into China and Japan and the diverse range of Buddhist masters who employed these esoteric techniques to achieve rebirth in Sukhavati, the Pure Land of Bliss. In Part II, he considers the life of Dohan and analyzes the monk's comprehensive view of buddhanusmrti as a form of ritual technology that unified body and mind, Sukhavati as a this-worldly or other-worldly soteriological goal synonymous with nirvana itself, and the Buddha Amitabha as an object of devotion beyond this world of suffering. The work concludes with the first full translation of Dohan's Himitsu nenbutsu sho into a modern language"--